Government Strategy in Empowering Farm Farmer Groups in Sidoarjo - Nofianti, Efa; Agustina, Isna Fitria (Universitas Muhammadiyah Sidoarjo, 2020)
To increase fishery products, it is done empowerment for pond farmers. The Implementation of Government Strategies in Empowering Tambak Farmer Groups in Jabon District, Sidoarjo Regency is inseparable from obstacles. The problems in implementing the program strategy are, firstly, the lack of number of Field Fishery Extension Officers (PPL) in empowering groups of pond farmers so that they are less effective in carrying out their duties. Second, the human resources of the pond farmers are very minimal, this is because the human resources of the pond farmers are primary and junior high school farmers. There are also some pond farmers who are apathetic in groups and have limited time in empowering pond farmer groups. This study aims to analyze the Government's Strategy for Empowerment of Tambak Farmers Groups in Jabon District, Sidoarjo Regency. The type of research used is descriptive qualitative. Data collection techniques are carried out through observation, interviews and documentation. Determination of informants using purposive sampling technique. The technique of analyzing data is done by collecting data, reducing data, presenting data, and drawing conclusions. The results of this study indicate that the Government's Strategy in Empowerment of Tambak Farmers Groups in Jabon District, Sidoarjo Regency is not yet optimal. It is indicated by the lack of fulfillment of indicators in the strategy process according to the strategy process according to AkxKootenx in Salususx (2006: 104-105), namely indicators of organizational strategy, program strategy, support strategies, resources and strategies. institutional.